IMPLEMENTASI E-GOVERNMENT MELALUI APLIKASI DEPOK SINGLE WINDOW DI KOTA DEPOK - Indriasari, Ratna; Prakosa, Alfriza Nadindra (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2023)
The Depok City Government responded to advances in information technology by launching an e-app. Government application, Depok Single Window (DSW), in August 2018. Despite its potential to improve public services, DSW faces several obstacles such as lack of evaluation, decline in users, unpreparedness in handling complaints, and lack of socialization. This research aims to find out the Implementation of e-government in improving public services through the Depok Single Window application in Depok City, Furthermore, to find out the supporting factors and inhibiting factors in the implementation of e-government. supporting factors and inhibiting factors in the implementation of e-government through the Depok Single Window application in Depok City, and to find out the efforts of the Depok City government in improving the implementation of e-government through the Depok Single Window application. Depok Single Window application. This research uses a qualitative method with a descriptive approach, focusing on the Depok City Communication and Informatics Office. Communication and Informatics Office of Depok City. Data collection was done through interviews, observation, and documentation. Data analysis techniques with data reduction, data presentation, conclusion drawing, and verification. verification. The results showed that First, the Depok City Government continues to innovate by implementing e-Government through the